TIPOLOGI KONSTRUKSI RUMAH TRADISIONAL “FALA GABA-GABA” SEBAGAI PERWUJUDAN BANGUNAN HEMAT ENERGI - Endah Harisun; M Amrin Ms Conoras; Hafid Saefudin (Fakultas Teknik Universitas Khairun, 2019)
Fala Gaba-gaba is a traditional house with most of the building material coming from sago trees. Where sago trees are plants that grow a lot in eastern Indonesia including Maluku, North Maluku and Papua. Made from natural materials, coupled with an opening arrangement that adapts to the local climate makes the traditional house